X-ray examination methods of veins of the human rectum - A. N. Russkikh; A. D. Shabokha (Бюллетень сибирской медицины, 2019)
The aim of this study is to determine the morphometric features of the vessels of the venous system of the rectum of men of different body types using the X-ray method. Materials and methods. To carry out X-ray contrast study of rectum veins in a direct projection of the pelvic organs was performed. Results. As a result of the study, it was established that the developed method of radiological examination of rectum veins, consisting of three consecutive photographs of the stage contrasting of the organ vessels, allows to determine the features of angioarchitectonics and the spatial arrangement of rectal vessels of corpses of men of different body types according to J.M. Tanner without extracting it. The maximum values of the corners of the formation of the second-order portal system of the corpus gynecomorphic somatotype male corpuscles, as well as the minimum values of the angles of vein formation of the first order of their caval system, the constancy of the loose type branching of the portal system parallel to the organ of the vessels, and the frequent occurrence of a single type of branching of the direct vascular organ in the absence of constitutional features branching of the vessels of the cadavers of the rectum of the investigated corpses of men. Conclusion. This finding can be used to assess the effect of venous outflow on the structural characteristics of the vascular system of the rectal wall, depending on the body type of the individual.